Research and Analysis on the Mutual Restriction Factors Between Green Finance and New Energy Power Industry - Zefeng Ruan; Keyuan Jin (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2023)
For the past few years, green finance, as one of the most important means of sustainable development, has been widely concerned by scholars at home and abroad. The development of new energy power industry is rapid, and the application of green finance is more and more extensive. The integration of the green finance and new energy power industry is conducive to promoting the construction of ecological civilization in China. However, due to the relatively backward development of green finance, the new energy power industry also has some limitations, resulting in defects in the integration of the two. This paper first describes the current situation of the support of green finance to the development of China's new energy power industry, and the mechanism of green finance supporting the new energy power industry, that is, the effect of capital aggregation and the effect of scientific and technological innovation. On this basis, it further analyzes the bottleneck constraints in the process of the two docking, such as insufficient supply of green financial products, low level of innovation, imperfect laws and regulations, etc. Finally, the paper puts forward some suggestions on how to realize the connection between new energy industry and power industry. The content is novel and frontier.